THE ROLE OF ARABIC LINGUISTICS IN EDUCATION AND SOCIOLOGY OF RELIGION: AN INTEGRATIVE APPROACH - Khairanis, Retisfa (International Journal of Multidisciplinary Reseach, 2025)
This research aims to examine the linguistic role of Arabic in education and the sociology of religion, focusing on how Arabic as a medium of religious communication can shape social and religious values in society. This study also explores the relevance of Arabic language teaching in strengthening religious understanding and building social harmony in the context of multicultural education. The research method used is a qualitative approach with literature study analysis and in-depth interviews with educators, linguists, and religious leaders. The data is analyzed through an interdisciplinary perspective between linguistics, education, and sociology of religion to gain a comprehensive understanding. The results show that Arabic not only serves as a religious language in the Islamic tradition, but also an important tool in building religious identity and social solidarity. Effective teaching of Arabic in educational institutions can improve religious literacy and strengthen cross-cultural understanding, thereby reducing conflicts based on religious and cultural differences. The implication of this study is the importance of linguistic integration of Arabic in the religious education curriculum as well as the development of language training programs based on sociological values. This study contributes to providing new insights into the role of language as a bridge between education and social harmony in a multicultural society.